(untitled) - Birkinshaw, Julian (Oxford, 2000)
This book provides a detailed account of the network-like organizational forms that some firms are adopting to make themselves more flexible and responsive to changing technologies and customer demands. As these organizations become more pervasive, the winners will be those firms that develop the specific capabilities that are needed to thrive in a networked world.
Keywords: Business networks,Strategic alliances (business),Organizational change,Organizational effectiveness